MECHANISM OF THE CONTEXTUAL APPROACH IN THE EXEGESIS OF THE QUR’AN - Ali Allouche, (International Journal of Innovative Technologies in Social Science, 2025)
There is no doubt that the contextual approach is a contemporary linguistic methodology, particularly in modern semantics, which has played a significant role in the study of texts. Accordingly, these new mechanisms can be applied to the exegesis of the Qur’anic texts while maintaining adherence to the general principles of the Qur’anic interpretation. This article examines the contextual approach and its mechanisms for understanding both the clear and the elusive aspects of the Qur'an. It addresses a specific question: does the study of Qur'anic texts via a contextual approach yield a new semantic dimension distinct from prior approaches? Do these new mechanisms offer linguists potential solutions to issues that have proven problematic? Does this, in turn, enrich linguistic research in general and Qur'anic studies in particular? Moreover, is it possible to benefit from modern linguistic studies in applying the contextual approach to the exegesis of its verses while taking into account the peculiarity of the Qur’anic text as being “divine in origin,” “Arabic in language,” and “universal in message”?